Labor market needs of pv installers: comparison of the situation in Ukraine and Bulgaria - Stoykova, Evelina; Nikolova, Nina; Kaplun, Victor; Makarevych, Svitlana; Shelimanova, Olena (Energy and Automation, 2024)
The implementation of the European Climate Law, the Energy Transition Roadmap until 2050 and the decarbonization scenario are the priority tasks of the European Commission in the field of energy effiшсіency and a political commitment to significant energy savings. Therefore, the task of training and retraining specialists in the field of "smart buildings", new technical solutions in the application of photovoltaic systems, etc., becomes especially urgent. This issue is the main goal of the project («Vocational Education and Training For Green and Smart Energ in Buildings» (VET4GSEB) The aim of the surveys conducted  within the framework of the Project in the partner-countries (Albania, Armenia, Bulgaria, Georgia, Turkey and Ukraine) was to examine the opinions, needs and expectations of companies and professionals involved in the renewable energy market on the state of this market and in particular the issues related to the efficiency and quality of installation and maintenance of systems, and the skills needed to achieve efficiency and quality, as well as to identify the needs of theoretical knowledge and practical skills of technicians and installers of geothermal and solar installations, for the purpose of tackling the identified gaps and needs by improving training curricula for the target groups and upskilling trainers.Key words:, renewable energy sources, photovoltaics technology, installers of PV-station